Improvement Of Basketball Learning Results Using Group Investigation Learning Model - Abdul Hanansyah; Agi Ginanjar (JUARA : Jurnal Olahraga, 2019)
The purpose of this study was to determine the Group Investigation learning model in physical education can improve student learning outcomes in basketball learning. The research method used classroom action research with the Kemmis & McTaggart model. The subjects in this study were students of class VIII-B SMP Negeri 1 Juntinyuat is 31 students. The research instrument used a test. Data analysis using descriptive statistics. The results stated that the Group Investigation learning model in physical education can improve student learning outcomes in basketball learning. In cycle I there is an increase in class averages 77.7 and as many as 68% of students reach KKM. In cycle II there is an increase in class averages 86.1 and as many as 100% of students reach KKM.